2014
DOI: 10.1002/ijc.28847
|View full text |Cite
|
Sign up to set email alerts
|

Treatment de‐escalation in HPV‐positive oropharyngeal carcinoma: Ongoing trials, critical issues and perspectives

Abstract: Due to the generally poor prognosis of head and neck squamous cell carcinoma (HNSCC), treatment has been intensified, these last decades, leading to an increase of serious side effects. High‐risk human papillomavirus (HR‐HPV) infection has been recently etiologically linked to a subset of oropharyngeal squamous cell carcinoma (OPSCC), which is on the increase. These tumors are different, at the clinical and molecular level, when compared to tumors caused by traditional risk factors. Additionally, their prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
168
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(173 citation statements)
references
References 66 publications
(72 reference statements)
2
168
0
3
Order By: Relevance
“…Furthermore, recent research has shown that patients with HPV-positive oropharyngeal tumours have a better prognosis (24)(25)(26). A favourable outcome for HPV-positive HNSCC patients could also be confirmed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, recent research has shown that patients with HPV-positive oropharyngeal tumours have a better prognosis (24)(25)(26). A favourable outcome for HPV-positive HNSCC patients could also be confirmed in this study.…”
Section: Discussionsupporting
confidence: 81%
“…24 Despite no significant difference in the receipt of concurrent chemotherapy (57.4% vs 58.9%), patients in the third group (T3-4 or N3) were significantly more likely to be g-tube dependent at 1 year than those in the second, 10.1% (95%CI: 7.9-12.3%) vs 5.2% (95%CI: 3.8-6.6%), reflecting an underlying difference in these two patient cohorts (Figure 3). …”
Section: Discussionmentioning
confidence: 99%
“…Treatment de-escalation may be attainable in patients with HPV-positive HNCUP, similar to that discussed for patients with HPV-positive oropharyngeal SCC (12). Still, before HPV status of HNCUP can be used to guide treatment, more knowledge on the biology and clinical behaviour of the disease is needed, especially due to the debate on whether CUP in different parts of the body share common traits or whether they behave more like normal metastases (13).…”
mentioning
confidence: 99%